(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2018)
Over the past few decades, the global phenomenology of political power has changed. Unlike what happened in the past, increasingly the practical applications of scientific discoveries are no longer immediately or exclusively used by the legally formalized political power. They are consumed and disseminated throughout civil society escaping from the old logic of the legitimate power or judicial power and generating a new political power, which could be defined as “glocal”. All these new dynamics can be better understood through the lenses offered by past philosophical dialogues on the same topics and in this case we can enrich our perspective from a discussion, which was developed in mid-twentieth century Italy. In 1950, the formal establishment of the Société Européenne de Culture took place in Venice with the hope of building a bridge between West and East political Europe. Through constant reflection on the general development of European society, this cultural institution tried to focus on priorities regarding theory and practice, in order to foster cultural positions that could take ethical-political responsibilities regarding understanding, collaboration and peace. This commitment was theoretically founded on the concept of “politics of culture”, formulated by Umberto Campagnolo and expressed in a session of the General Assembly in November 1951 and later in January of 1952, Norberto Bobbio gave notice of it in the “Rivista di Filosofia” (“Journal of Philosophy”), sharing the principles expressed by Campagnolo. The theoretical dialogue between the two philosophers intensified at the beginning of the 60s, when it became clear that the common civil commitment sprang from a different conception of philosophy and politics.